Human Rights Juridic Review on Transgenders as a Tool of Social Control in Indonesia - Sihombing, Saling Sabrina (Jurnal Scientia Indonesia, 2020)
This study discusses how to apply human rights law as a means of social control over gender in Indonesia, how to treat and improve the community for transgender people in Indonesia, the inhibiting factors for implementing protection for transgender people in Indonesia and how to respect the rights of transgender groups.  The method used in this scientific article is a normative-empirical legal research method.  The normative-empirical legal research method is basically a combination of a normative legal approach or based on statutory regulations with the addition of various empirical elements or seeing every legal event within the scope of the general public.  It can be concluded that the normative-empirical legal research method is an approach or implementation of normative law in every aspect of legal events that occur in the community.  The aim is to find out the importance of providing protection to transgender people as Indonesian citizens and further about legal protection for transgender people and how it is implemented.  From the results of the study, it can be seen that legal protection as an Indonesian citizen from discrimination has indeed been running but has not been maximized.  The problem with providing protection to transgender people is that there is still no firm stance from the government in dealing with the issue of protection for transgender people and the absence of legal regulations specifically made for transgender conditions and the attitude of people who are still indifferent to transgender people.